NEED SATISFACTION AND SOCIAL ADJUSTMENT OF DEAF AND DUMB CHILDREN IN FAISALABAD - S. Nadir; S. Akhtar; M. Ali (Journal of Animal and Plant Sciences, 2006)
A study was carried out to assess the needs of deaf and dumb children of teenage and how these needs must be satisfied that these children will be well adjusted in society. A well-designed interview schedule was used to interview them. The number of male (170) children was slightly higher than female children in hearing impaired children school. A sample of 120 respondents was selected from the two Government Higher Secondary Schools of Special Education located at Peoples Colony and Jaranwala Road, Faisalabad. Majority of the children i.e. 80% were deaf and dumb by birth. Sixty Percent of the disabled children belonged to age category 17-19 years. The children who received proper attention by their parents and teachers were well adjusted in the society, as they did not hesitate and feel shyness in meeting strangers. On the other hand those children who did not receive proper attention by their parents and teachers created the problem of maladjustment in society.
Keywords: Need satisfaction; Social adjustment; deaf and dumb